Advertising and Promotions in the US Green Industry: FE948/FE948, 8/2014 - Khachatryan, Hayk; Rihn, Alicia; Palma, Marco A.; Hall, Charles R. (EDIS, 2014)
US firms that sell nursery and garden products have become more interested in effective advertising and promotion strategies. A major question for these green industry firms is how to stimulate additional sales. This 3-page fact sheet was written by Hayk Khachatryan, Alicia Rihn, Marco A. Palma, and Charles R. Hall, and published by the UF Department of Food and Resource Economics, August 2014. FE948/FE948: Advertising and Promotions in the US Green Industry (ufl.edu)